Heat-shrinkable film and heat-shrinkable label

JP2025028278APending Publication Date: 2025-02-28GUNZE LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024221778
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-02-28

AI Technical Summary

Benefits of technology

【0070】 本発明によれば、化石資源の使用量を削減することができるとともに、機械的特性等の物性面において高い性能を発現可能な熱収縮性フィルムを提供することができる。また、該熱収縮性フィルムを含む熱収縮性ラベルを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025028278000001
    Figure 2025028278000001
Patent Text Reader

Abstract

To provide a heat-shrinkable multilayer film that can reduce an amount of use of fossil resources and can express high performance in physical properties such as mechanical properties, and a heat-shrinkable label having the heat-shrinkable multilayer film.SOLUTION: A heat-shrinkable film has at least one of a layer containing a polyester resin and a layer containing a polystyrenic resin, the heat-shrinkable film containing a biomass-derived component.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a heat-shrinkable film that can reduce the amount of fossil resources used and exhibits high performance in terms of physical properties such as mechanical properties, etc. The present invention also relates to a heat-shrinkable label including the heat-shrinkable film. [Background technology]

[0002] 2. Description of the Related Art In recent years, heat-shrinkable labels formed by printing or the like on a base film made of a thermoplastic resin are attached to many containers such as PET bottles and glass bottles. For heat-shrinkable labels, polystyrene-based resin films, which have excellent low-temperature shrinkability, and polyester-based resin films, which have excellent heat resistance and solvent resistance, are often used. Also, in order to have both of these properties, a multi-layer film having front and back layers containing a polyester resin and an intermediate layer containing a polystyrene resin has been investigated.

[0003] On the other hand, in recent years, there has been an increasing demand for the creation of a recycling-based, low-carbon society in order to realize a sustainable society, and there is a desire to move away from reliance on fossil resources. However, conventional general-purpose plastics such as polyester resins and polystyrene resins all use petroleum resources as raw materials, and therefore face problems such as the depletion of petroleum resources and the generation of harmful gases when used continuously.

[0004] In response to these problems, attempts are being made to produce polyester resins, which are general-purpose plastics, from biomass raw materials. For example, Patent Document 1 discloses a method for producing resin raw materials such as ethylene glycol and terephthalic acid using biomass as a raw material. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2007-176873 A Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention aims to provide a heat-shrinkable film that can reduce the amount of fossil resources used and exhibits high performance in terms of physical properties such as mechanical properties, etc. It also aims to provide a heat-shrinkable label containing the heat-shrinkable film. [Means for solving the problem]

[0007] The present invention relates to a heat-shrinkable film having at least one layer selected from the group consisting of a layer containing a polyester-based resin and a layer containing a polystyrene-based resin, the heat-shrinkable film containing a component derived from biomass. The present invention will be described in detail below.

[0008] The present inventors have found that, in a heat-shrinkable film having at least one layer selected from a layer containing a polyester-based resin and a layer containing a polystyrene-based resin, even when a resin containing a component derived from biomass is used, the heat-shrinkable film can exhibit high performance in terms of physical properties such as mechanical properties. Note that "biomass" refers to "renewable organic resources derived from living organisms, excluding fossil resources." Therefore, the inventors have found that it is possible to reduce the amount of raw materials obtained from fossil resources and to reduce the amount of fossil resources used, as compared to the conventional method, and have thus completed the present invention.

[0009] The heat-shrinkable film of the present invention has at least one layer selected from the group consisting of a layer containing a polyester-based resin and a layer containing a polystyrene-based resin. The heat-shrinkable film of the present invention may consist only of a layer containing a polyester-based resin, may consist only of a layer containing a polystyrene-based resin, or may have front and back layers containing a polyester-based resin and an intermediate layer containing a polystyrene-based resin. Furthermore, when the heat-shrinkable film of the present invention consists only of a layer containing a polyester-based resin, it may have only one layer containing the polyester-based resin, or it may have two or more layers. Furthermore, when the heat-shrinkable film of the present invention consists only of a layer containing a polystyrene-based resin, it may have only one layer containing the above-mentioned polystyrene-based resin, or it may have two or more layers. In this specification, the front and back layers refer to both the front layer and the back layer.

[0010] When the heat-shrinkable film of the present invention has a front and back layer and an intermediate layer, it is sufficient that at least one of the polyester-based resin constituting the front and back layers and the polystyrene-based resin constituting the intermediate layer contains a biomass-derived component; only the polyester-based resin constituting the front and back layers may contain a biomass-derived component, only the polystyrene-based resin constituting the intermediate layer may contain a biomass-derived raw material, or both the polyester-based resin and the polystyrene-based resin may contain a biomass-derived component. Whether or not the polyester-based resin and the polystyrene-based resin contain components derived from biomass can be confirmed by the presence or absence of radioactive carbon (C14) in the resin. Carbon dioxide in the atmosphere contains a certain percentage of C14 (105.5 pMC), so it is known that the C14 content in plants that grow by absorbing carbon dioxide from the atmosphere is also about 105.5 pMC. It is also known that fossil resources contain very little C14. Therefore, by measuring the percentage of C14 in the total carbon atoms in polyester resins and polystyrene resins, it is possible to confirm whether or not they contain components derived from biomass. The presence or absence of the radioactive carbon (C14) can be confirmed, for example, by using a method similar to that for measuring the biomass degree described below.

[0011] When the heat-shrinkable film of the present invention is composed only of a layer containing the above-mentioned polyester-based resin, the polyester-based resin constituting the layer containing the above-mentioned polyester-based resin may be composed only of a polyester-based resin containing a component derived from biomass, or may contain a polyester-based resin containing a component derived from biomass and a polyester-based resin not containing a component derived from biomass. In addition, when the heat-shrinkable film of the present invention has the front and back layers and the intermediate layer, the polyester-based resin constituting the layer containing the polyester-based resin may contain a biomass-derived component or may not contain a biomass-derived component. In addition, the polyester-based resin may contain a polyester-based resin containing a biomass-derived component and a polyester-based resin not containing a biomass-derived component.

[0012] The polyester-based resin constituting the layer containing the polyester-based resin may be, for example, one obtained by polycondensation of a dicarboxylic acid component and a diol component. In the case where the polyester-based resin contains a biomass-derived component, the polyester-based resin may contain a biomass-derived dicarboxylic acid component, may contain a biomass-derived diol component, or may contain both a biomass-derived dicarboxylic acid component and a biomass-derived diol component.

[0013] Examples of the dicarboxylic acid include terephthalic acid, o-phthalic acid, isophthalic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, octyl succinic acid, cyclohexanedicarboxylic acid, naphthalenedicarboxylic acid, fumaric acid, maleic acid, itaconic acid, decamethylene carboxylic acid, anhydrides and lower alkyl esters thereof. As the dicarboxylic acid, terephthalic acid and isophthalic acid are preferred.

[0014] In 100 mol % of the above dicarboxylic acid component, the component derived from terephthalic acid is preferably contained in an amount of 50 to 100 mol %, and more preferably contained in an amount of 60 to 100 mol %. In addition, the dicarboxylic acid component preferably contains 0 to 50 mol %, and more preferably 0 to 40 mol %, of a component derived from isophthalic acid, relative to 100 mol % of the dicarboxylic acid component.

[0015] Examples of the diol include ethylene glycol, 1,3-propanediol, 1,4-butanediol, diethylene glycol, 1,5-pentanediol, 1,6-hexanediol, dipropylene glycol, triethylene glycol, tetraethylene glycol, 1,2-propanediol, 1,3-butanediol, 2,3-butanediol, neopentyl glycol (2,2-dimethylpropane-1,3-diol), 1,2-hexanediol, 2,5- Examples of the diols include aliphatic diols such as hexanediol, 2-methyl-2,4-pentanediol, 3-methyl-1,3-pentanediol, 2-ethyl-1,3-hexanediol, and polytetramethylene ether glycol; and alicyclic diols such as 2,2-bis(4-hydroxycyclohexyl)propane, alkylene oxide adducts of 2,2-bis(4-hydroxycyclohexyl)propane, 1,4-cyclohexanediol, and 1,4-cyclohexanedimethanol. The diol is preferably ethylene glycol, 1,4-butanediol, diethylene glycol, or 1,4-cyclohexanedimethanol.

[0016] In 100 mol % of the above diol component, the component derived from ethylene glycol is preferably contained in an amount of 40 to 100 mol %, and more preferably contained in an amount of 50 to 100 mol %. In 100 mol % of the above diol component, the component derived from diethylene glycol is preferably contained in an amount of 0 to 40 mol %, and more preferably 0 to 30 mol %. In 100 mol % of the above diol component, the component derived from 1,4-cyclohexanedimethanol is contained in an amount of preferably 0 to 70 mol %, and more preferably 0 to 60 mol %.

[0017] The diol component may contain a component derived from biomass. In particular, as the diol component derived from biomass, it is preferable that the diol component contains a component derived from ethylene glycol, 1,4-butanediol, diethylene glycol, or 1,4-cyclohexanedimethanol, and it is more preferable that the diol component contains a component derived from ethylene glycol. The biomass-derived ethylene glycol may be one that uses biomass ethanol produced from biomass as a raw material. For example, the biomass-derived ethylene glycol may be produced from biomass ethanol by a conventional method.

[0018] The content of the biomass-derived component in the diol component is preferably 30 mol % or more, more preferably 50 mol % or more, and is preferably 100 mol % or less. By setting the content within the above range, there is an advantage in that the environmental load is reduced.

[0019] The content of biomass-derived ethylene glycol in the diol component is preferably 30 mol % or more, more preferably 50 mol % or more, and is preferably 100 mol % or less.

[0020] The biomass degree of the polyester resin is preferably 1% or more, more preferably 5% or more, and is preferably 100% or less. By setting the content within the above range, there is an advantage in that the environmental load is reduced. The biomass degree is a value obtained by measuring the content of original biomass-derived substances by radioactive carbon (C14) measurement. The biomass degree can be measured using an accelerator mass spectrometer based on ISO16620-2:2015.

[0021] The polyester resin may contain a plurality of polyester resins having different biomass degrees. When the polyester resin is a mixed resin containing a plurality of polyester resins with different biomass degrees, the biomass degree of the mixed resin can be measured based on ISO16620-2: 2015. The biomass degree can also be calculated based on the weight ratio and biomass degree of each polyester resin in the mixed resin.

[0022] When the polyester-based resin contains a polyester-based resin containing a biomass-derived component, the content of the polyester-based resin containing a biomass-derived component in the polyester-based resin is preferably 5% by weight in lower limit, more preferably 10% by weight in lower limit, and preferably 100% by weight in upper limit.

[0023] The lower limit of the glass transition temperature of the polyester resin is preferably 55°C, and the upper limit is preferably 95°C. If the glass transition temperature is less than 55°C, the shrinkage start temperature of the heat-shrinkable multilayer film may be too low, the natural shrinkage rate may be large, and blocking may be easily caused. If the glass transition temperature is more than 95°C, the low-temperature shrinkability and shrink finish of the heat-shrinkable multilayer film may be reduced, the low-temperature shrinkability may be significantly reduced over time, and resin whitening may be easily caused during stretching. The lower limit of the glass transition temperature is more preferably 60°C, and the upper limit is more preferably 90°C. The lower limit is even more preferably 65°C, and the upper limit is even more preferably 85°C. The glass transition temperature can be measured by a method in accordance with ISO 3146. When the polyester resin is a mixed resin containing a plurality of polyester resins having different glass transition temperatures, the glass transition temperature of the mixed resin means an apparent glass transition temperature calculated based on the weight ratio and glass transition temperature of each polyester resin in the mixed resin.

[0024] The lower limit of the tensile modulus of the polyester resin is preferably more than 1000 MPa, and the upper limit is preferably 4000 MPa. If the tensile modulus is 1000 MPa or less, the shrinkage start temperature of the heat shrinkable film may be too low, or the natural shrinkage rate may be large. If the tensile modulus is more than 4000 MPa, the low-temperature shrinkability and shrink finish of the heat shrinkable multilayer film may be reduced, or the low-temperature shrinkability may be significantly reduced over time. The lower limit of the tensile modulus is more preferably 1500 MPa, and the upper limit is more preferably 3700 MPa. The tensile modulus can be measured by a method in accordance with ASTM-D882 (Test A).

[0025] As the polyester-based resin constituting the layer containing the polyester-based resin, a polyester-based resin having the above-mentioned composition may be used alone, or two or more polyester-based resins having the above-mentioned composition may be used in combination.

[0026] The layer containing the polyester resin may contain additives such as antioxidants, heat stabilizers, ultraviolet absorbers, light stabilizers, lubricants, antistatic agents, antiblocking agents, flame retardants, antibacterial agents, fluorescent brightening agents, and colorants, as necessary.

[0027] When the heat-shrinkable film of the present invention is composed only of a layer containing the above-mentioned polystyrene-based resin, the polystyrene-based resin constituting the layer containing the above-mentioned polystyrene-based resin may be composed only of a polystyrene-based resin containing a component derived from biomass, or may contain a polystyrene-based resin containing a component derived from biomass and a polystyrene-based resin not containing a component derived from biomass. In addition, when the heat-shrinkable film of the present invention has the above-mentioned front and back layers and intermediate layer, the polystyrene-based resin constituting the layer containing the polystyrene-based resin may contain a biomass-derived component or may not contain a biomass-derived component. In addition, the polystyrene-based resin may contain a polystyrene-based resin containing a biomass-derived component and a polystyrene-based resin not containing a biomass-derived component.

[0028] Examples of the polystyrene resin constituting the layer containing the polystyrene resin include aromatic vinyl hydrocarbon-conjugated diene copolymer, a mixed resin of aromatic vinyl hydrocarbon-conjugated diene copolymer and aromatic vinyl hydrocarbon-aliphatic unsaturated carboxylic acid ester copolymer, rubber-modified impact resistant polystyrene, etc. By using the polystyrene resin, the heat shrinkable multilayer film of the present invention can start shrinking at a low temperature and has high shrinkability.

[0029] In this specification, the aromatic vinyl hydrocarbon-conjugated diene copolymer refers to a copolymer containing a component derived from an aromatic vinyl hydrocarbon and a component derived from a conjugated diene. The aromatic vinyl hydrocarbon-derived component may contain a biomass-derived component. Furthermore, the conjugated diene-derived component may contain a biomass-derived component. The aromatic vinyl hydrocarbon is not particularly limited, and examples thereof include styrene, o-methylstyrene, p-methylstyrene, etc. These may be used alone or in combination of two or more kinds. The conjugated diene is not particularly limited, and examples thereof include 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 1,3-hexadiene, etc. These may be used alone or in combination of two or more.

[0030] The aromatic vinyl hydrocarbon-conjugated diene copolymer preferably contains a styrene-butadiene copolymer (SBS resin) because of its excellent heat shrinkability. In order to produce a heat shrinkable multilayer film with fewer fisheyes, the aromatic vinyl hydrocarbon-conjugated diene copolymer preferably contains a styrene-isoprene copolymer (SIS resin) using 2-methyl-1,3-butadiene (isoprene) as the conjugated diene, a styrene-isoprene-butadiene copolymer (SIBS), or the like. The aromatic vinyl hydrocarbon-conjugated diene copolymer may contain any one of SBS resin, SIS resin and SIBS resin alone or a combination of two or more. When two or more of SBS resin, SIS resin and SIBS resin are used, the resins may be dry blended, or a compound resin may be used in which the resins are kneaded in a specific composition using an extruder and pelletized.

[0031] In the aromatic vinyl hydrocarbon component, the content of the biomass-derived component is preferably 5% by weight or more, more preferably 30% by weight or more, and is preferably 100% by weight or less. Furthermore, the content of the biomass-derived component in the above-mentioned conjugated diene component is preferably 5% by weight or more, more preferably 30% by weight or more, and is preferably 100% by weight or less.

[0032] The polystyrene resin preferably has a styrene component content of 65% by weight or more, more preferably 70% by weight or more, and preferably 90% by weight or less, more preferably 85% by weight or less. When the styrene content is 65% by weight or more, foreign matter such as gel is unlikely to be generated during molding processing, and the mechanical strength of the heat-shrinkable film can be sufficiently increased.When the styrene content is 90% by weight or less, breakage when tension is applied to the heat-shrinkable film or during processing such as printing can be prevented.

[0033] The polystyrene resin preferably contains a styrene component derived from biomass. The biomass-derived styrene may be one that uses ethylene produced from biomass-derived naphtha as a raw material. For example, the biomass-derived styrene may be produced from biomass-derived naphtha as a raw material by a conventionally known method.

[0034] When the polystyrene-based resin contains a biomass-derived styrene component, the content of the biomass-derived styrene component in the polystyrene-based resin is preferably 5% by weight or more, more preferably 30% by weight or more, and is preferably 100% by weight or less.

[0035] The polystyrene resin preferably has a conjugated diene content of 10% by weight or more, more preferably 15% by weight or more, and preferably 35% by weight or less, more preferably 30% by weight or less.

[0036] The polystyrene-based resin preferably contains a conjugated diene component derived from biomass, and more preferably contains a butadiene component derived from biomass. The biomass-derived butadiene may be produced using naphtha derived from biomass as a raw material. For example, the biomass-derived butadiene may be produced using a conventionally known method using naphtha derived from biomass as a raw material.

[0037] When the polystyrene-based resin contains a biomass-derived conjugated diene component, the content of the biomass-derived conjugated diene component in the polystyrene-based resin is preferably 5% by weight or more, more preferably 30% by weight or more, and is preferably 100% by weight or less.

[0038] When the polystyrene-based resin contains a biomass-derived butadiene component, the content of the biomass-derived butadiene component in the polystyrene-based resin is preferably 5% by weight or more, more preferably 30% by weight or more, and is preferably 100% by weight or less.

[0039] The content of the biomass-derived component in the polystyrene-based resin is preferably 5% by weight or more, more preferably 30% by weight or more, and is preferably 100% by weight or less.

[0040] The biomass ratio of the polystyrene resin is preferably 10% or more, more preferably 30% or more, and is preferably 100% or less. The biomass degree can be measured using an accelerator mass spectrometer based on ISO16620-2:2015.

[0041] The polystyrene-based resin may contain a plurality of polystyrene-based resins having different biomass degrees. When the polystyrene resin is a mixed resin containing a plurality of polystyrene resins with different biomass degrees, the biomass degree of the mixed resin can be measured based on ISO16620-2: 2015. The biomass degree can also be calculated based on the weight ratio and biomass degree of each polystyrene resin in the mixed resin.

[0042] The Vicat softening temperature of the polystyrene resin is preferably 60°C as a lower limit, and 85°C as an upper limit. If the Vicat softening temperature is less than 60°C, the low-temperature shrinkability of the heat-shrinkable multilayer film becomes too high, and wrinkles are likely to occur when the film is attached to a container. If the Vicat softening temperature exceeds 85°C, the low-temperature shrinkability of the heat-shrinkable multilayer film decreases, and unshrunk portions are likely to occur when the film is attached to a container. The Vicat softening temperature is more preferably 65°C as a lower limit, and 80°C as an upper limit. The Vicat softening temperature can be measured by a method in accordance with ISO 306:1994. In addition, when the polystyrene-based resin is a mixed resin containing a plurality of polystyrene-based resins having different Vicat softening temperatures, the Vicat softening temperature of the mixed resin means an apparent Vicat softening temperature calculated based on the weight ratio and Vicat softening temperature of each polystyrene-based resin in the mixed resin.

[0043] The polystyrene resin preferably has a lower limit of 2 g / 10 min and an upper limit of 15 g / 10 min for the MFR (melt flow rate) at 200° C. If the MFR at 200° C. is less than 2 g / 10 min, it becomes difficult to form a film. If the MFR at 200° C. is more than 15 g / 10 min, the mechanical strength of the film becomes low and it becomes unsuitable for practical use. The more preferred lower limit of the MFR at 200° C. is 4 g / 10 min and the more preferred upper limit is 12 g / 10 min. The MFR can be measured by a method conforming to ISO1133.

[0044] The layer containing the polystyrene-based resin may contain additives such as antioxidants, heat stabilizers, ultraviolet absorbers, light stabilizers, lubricants, antistatic agents, flame retardants, antibacterial agents, fluorescent brightening agents, and colorants, as necessary.

[0045] When the heat-shrinkable film of the present invention has the above-mentioned front and back layers and intermediate layer, the heat-shrinkable film of the present invention may consist of the front and back layers and the intermediate layer, and an adhesive layer may be interposed between the front and back layers and the intermediate layer.

[0046] The resin constituting the adhesive layer may be an adhesive resin such as a styrene-based elastomer, a polyester-based elastomer, or a modified product thereof. Also, a mixed resin of a polyester resin, a polystyrene resin, and a polyester elastomer can be used.

[0047] The styrene-based elastomer is a material consisting of polystyrene as a hard segment and polybutadiene, polyisoprene, or a copolymer of polybutadiene and polyisoprene as a soft segment, or a hydrogenated product thereof. The hydrogenated product may be a product in which the polybutadiene or polyisoprene is partially or entirely hydrogenated.

[0048] Commercially available examples of the styrene-based elastomer include "Tuftec" and "Tufprene" (both manufactured by Asahi Kasei Chemicals Corporation), "Kraton" (manufactured by Kraton Polymer Japan), "Dynaron" (manufactured by JSR Corporation), and "Septon" (manufactured by Kuraray Co., Ltd.).

[0049] Examples of the modified styrene-based elastomer include those modified with functional groups such as a carboxylic acid group, an acid anhydride group, an amino group, an epoxy group, and a hydroxyl group. The content of the functional groups such as carboxylic acid groups, acid anhydride groups, amino groups, epoxy groups, and hydroxyl groups in the modified styrene-based elastomer is preferably 0.05% by weight at the lower limit and 5.0% by weight at the upper limit. If the content is less than 0.05% by weight, the adhesion to the front layer and back layer may be insufficient, and if it exceeds 5.0% by weight, the resin may be thermally deteriorated when the functional groups are added, and foreign matter such as gel may be easily generated. The more preferable lower limit of the content is 0.1% by weight, and the more preferable upper limit is 3.0% by weight.

[0050] The polyester elastomer is preferably a saturated polyester elastomer, and particularly preferably a saturated polyester elastomer containing a polyalkylene ether glycol segment. As the saturated polyester elastomer containing a polyalkylene ether glycol segment, for example, a block copolymer consisting of an aromatic polyester as a hard segment and a polyalkylene ether glycol or an aliphatic polyester as a soft segment is preferable. Furthermore, a polyester polyether block copolymer having a polyalkylene ether glycol as a soft segment is more preferable.

[0051] The polyester polyether block copolymer is preferably one obtained by polycondensing an oligomer obtained by esterification or transesterification using as raw materials (i) an aliphatic and / or alicyclic diol having 2 to 12 carbon atoms, (ii) an aromatic dicarboxylic acid and / or an aliphatic dicarboxylic acid or an alkyl ester thereof, and (iii) a polyalkylene ether glycol.

[0052] The aliphatic and / or alicyclic diol having 2 to 12 carbon atoms may be, for example, one generally used as a raw material for polyesters, particularly raw materials for polyester-based elastomers. Specific examples include ethylene glycol, propylene glycol, trimethylene glycol, 1,4-butanediol, 1,4-cyclohexanediol, and 1,4-cyclohexanedimethanol. Among these, 1,4-butanediol or ethylene glycol is preferred, and 1,4-butanediol is particularly preferred. These diols may be used alone or in combination of two or more.

[0053] The aromatic dicarboxylic acid may be one that is generally used as a raw material for polyesters, particularly polyester elastomers. Specific examples include terephthalic acid, isophthalic acid, phthalic acid, and 2,6-naphthalenedicarboxylic acid. Among these, terephthalic acid or 2,6-naphthalenedicarboxylic acid is preferred, and terephthalic acid is particularly preferred. These aromatic dicarboxylic acids may be used alone or in combination of two or more.

[0054] Examples of the alkyl esters of the aromatic dicarboxylic acids include dimethyl esters and diethyl esters of the aromatic dicarboxylic acids, among which dimethyl terephthalate and 2,6-dimethylnaphthalenedicarboxylate are preferred.

[0055] The aliphatic dicarboxylic acid is preferably cyclohexanedicarboxylic acid, etc., and its alkyl ester is preferably dimethyl ester, diethyl ester, etc. In addition to the above components, a small amount of a trifunctional alcohol, tricarboxylic acid, or its ester may be copolymerized, and further, an aliphatic dicarboxylic acid such as adipic acid or its dialkyl ester may be used as a copolymerization component.

[0056] Examples of the polyalkylene ether glycol include polyethylene glycol, poly(1,2- and / or 1,3-propylene ether) glycol, poly(tetramethylene ether) glycol, and poly(hexamethylene ether) glycol.

[0057] The preferred lower limit of the number average molecular weight of the polyalkylene ether glycol is 400, and the preferred upper limit is 6000. By setting the number average molecular weight to 400 or more, the blockiness of the copolymer is increased, and by setting the number average molecular weight to 6000 or less, phase separation in the system is unlikely to occur, and polymer properties are easily expressed. The more preferred lower limit of the number average molecular weight is 500, the more preferred upper limit is 4000, the even more preferred lower limit is 600, and the even more preferred upper limit is 3000. In this specification, the number average molecular weight refers to that measured by gel permeation chromatography (GPC). The calibration of the GPC can be performed, for example, by using a POLYTETRAHYDROFURAN calibration kit (manufactured by POLYMER LABORATORIES, UK).

[0058] In addition, when the adhesive layer contains a mixed resin of a polyester resin, a polystyrene resin, and a polyester elastomer, the polyester resin may be the same as the polyester resin constituting the layer containing the polyester resin, and the polystyrene resin may be the same as the polystyrene resin constituting the layer containing the polystyrene resin. The polyester-based resin constituting the adhesive layer may contain a component derived from biomass, or may not contain a component derived from biomass. The polystyrene-based resin constituting the adhesive layer may contain a component derived from biomass, or may not contain a component derived from biomass.

[0059] In the heat shrinkable film of the present invention, the biomass degree has a preferred lower limit of 1%, a more preferred lower limit of 2%, and a still more preferred lower limit of 10%, and a preferred upper limit of 100%, a more preferred upper limit of 95%, and a still more preferred upper limit of 50%. By setting the content within the above range, there is an advantage that it is possible to reduce the environmental load without impairing the economic rationality or film performance. The biomass degree can be measured using an accelerator mass spectrometer based on ISO16620-2:2015.

[0060] The preferred lower limit of the thickness of the heat shrinkable film of the present invention is 30 μm, and the preferred upper limit is 60 μm. By setting the thickness of the heat shrinkable multilayer film within the above range, it is economical and easy to handle.

[0061] In addition, when the heat shrinkable film of the present invention has a front and back layer and an intermediate layer, the preferred lower limit of the thickness of the intermediate layer when the total thickness of the heat shrinkable film of the present invention is 45 μm is 22 μm, and the preferred upper limit is 37 μm. If it is 22 μm or more, sufficient perforations can be provided, and if it is 37 μm or less, sufficient heat resistance can be provided. The more preferred lower limit is 26 μm, and the more preferred upper limit is 36 μm. When the heat shrinkable film of the present invention has a front and back layer and an intermediate layer, the preferred lower limit of the thickness of the front and back layer when the total thickness of the heat shrinkable film of the present invention is 45 μm is 3 μm, and the preferred upper limit is 10 μm. If it is 3 μm or more, sufficient oil resistance and heat resistance can be imparted, and if it is 10 μm or less, sufficient cuttability at the perforation can be imparted. The more preferred lower limit is 4 μm, and the more preferred upper limit is 8 μm. When the heat shrinkable film of the present invention has a front and back layer and an intermediate layer, the preferred lower limit of the thickness of the adhesive layer when the total thickness of the heat shrinkable film of the present invention is 45 μm is 0.7 μm, and the preferred upper limit is 1.5 μm. If it is 0.7 μm or more, sufficient adhesive strength can be imparted, and if it is 1.5 μm or less, sufficient heat shrinkability can be imparted. The more preferred lower limit is 0.8 μm, and the more preferred upper limit is 1.3 μm.

[0062] Regarding the heat shrinkage properties of the heat shrinkable film of the present invention, when immersed in warm water at 70° C. for 10 seconds, the heat shrinkage rate in the MD direction (direction perpendicular to the main shrinkage direction) is preferably −12% at the lower limit, more preferably −7% at the lower limit, and preferably 8% at the upper limit, more preferably 3% at the upper limit, and the heat shrinkage rate in the TD direction (main shrinkage direction) is preferably 5% at the lower limit, more preferably 10% at the lower limit, and preferably 65% ​​at the upper limit, more preferably 50% at the upper limit. By setting the thickness within the above range, deformation of the container can be prevented, and rapid shrinkage due to heating can be prevented, thereby suppressing the occurrence of wrinkles and the like. The heat shrinkage rate when immersed in 70°C warm water for 10 seconds is the percentage change in dimensions after heating compared to the dimensions before heat treatment, obtained by cutting a sample of the heat-shrinkable multilayer film into a size of 100 mm x 100 mm and immersing it in 70°C warm water for 10 seconds.

[0063] Regarding the heat shrinkage properties of the heat shrinkable film of the present invention, when immersed in 80° C. warm water for 10 seconds, the heat shrinkage rate in the MD direction (direction perpendicular to the main shrinkage direction) is preferably −12% at the lower limit, more preferably −7% at the lower limit, and preferably 8% at the upper limit, more preferably 3% at the upper limit. Also, the heat shrinkage rate in the TD direction (main shrinkage direction) is preferably 35% at the lower limit, more preferably 45% at the lower limit, and preferably 70% at the upper limit, more preferably 65% ​​at the upper limit. The heat shrinkage rate when immersed in 80°C warm water for 10 seconds is the percentage change in dimensions after heating compared to the dimensions before heat treatment, obtained by cutting a sample of the heat-shrinkable multilayer film into a size of 100 mm x 100 mm and immersing it in 80°C warm water for 10 seconds.

[0064] Regarding the heat shrinkage properties of the heat shrinkable film of the present invention, when immersed in 90° C. warm water for 10 seconds, the heat shrinkage rate in the MD direction (direction perpendicular to the main shrinkage direction) is preferably −10% at the lower limit, more preferably −5% at the lower limit, and preferably 15% at the upper limit, more preferably 10% at the upper limit, and the heat shrinkage rate in the TD direction (main shrinkage direction) is preferably 50% at the lower limit, more preferably 55% at the lower limit, and preferably 80% at the upper limit, more preferably 75% at the upper limit. The heat shrinkage rate when immersed in 90°C warm water for 10 seconds is the percentage change in dimensions after heating compared to the dimensions before heat treatment, obtained by cutting a sample of the heat-shrinkable multilayer film into a size of 100 mm x 100 mm and immersing it in 90°C warm water for 10 seconds.

[0065] Regarding the heat shrinkage properties of the heat shrinkable film of the present invention, when immersed in 98° C. warm water for 10 seconds, the heat shrinkage rate in the MD direction (direction perpendicular to the main shrinkage direction) is preferably 0% at the lower limit, more preferably 5% at the lower limit, and preferably 25% at the upper limit, more preferably 20% at the upper limit, and the heat shrinkage rate in the TD direction (main shrinkage direction) is preferably 55% at the lower limit, more preferably 65% ​​at the lower limit, and preferably 85% at the upper limit, more preferably 80% at the upper limit. The heat shrinkage rate when immersed in 98°C warm water for 10 seconds is the percentage change in dimensions after heating compared to the dimensions before heat treatment, obtained by cutting a sample of the heat-shrinkable multilayer film into a size of 100 mm x 100 mm and immersing it in 98°C warm water for 10 seconds.

[0066] The natural shrinkage rate in the TD direction of the heat-shrinkable film of the present invention is preferably 3% when left at 40° C. for 7 days. If the natural shrinkage rate is 3% or less, the heat-shrinkable film of the present invention is less likely to undergo dimensional change during storage, and defects during printing processing can be prevented. The more preferred upper limit of the natural shrinkage rate is 2%.

[0067] The method for producing the heat shrinkable film of the present invention is not particularly limited, but a method in which each layer is simultaneously formed by a co-extrusion method is suitable. For example, in the case of co-extrusion using a T-die, the lamination method may be any of a feed block method, a multi-manifold method, or a method using both of these. Specifically, for example, a method can be used in which the raw materials constituting the layer containing a polyester resin, the raw materials constituting the layer containing a polystyrene resin, and the raw materials constituting the adhesive layer as necessary are each fed into an extruder, extruded into a sheet shape by a die, cooled and solidified by a take-up roll, and then stretched uniaxially or biaxially.

[0068] A heat-shrinkable label can be obtained by using the heat-shrinkable film of the present invention as a base film. Such a heat-shrinkable label also constitutes the present invention. The heat-shrinkable label of the present invention may have the above-mentioned heat-shrinkable multilayer film as a base film, and other layers such as a printed layer may be laminated thereon, if necessary.

[0069] The usual method for attaching a heat-shrinkable label to a container involves using a solvent to bond the ends of a heat-shrinkable multilayer film and processing it into a tubular shape (center seal processing) to make a heat-shrinkable label, which is then heated while covering the container to cause it to shrink. Effect of the Invention

[0070] According to the present invention, it is possible to provide a heat-shrinkable film that can reduce the amount of fossil resources used and can exhibit high performance in terms of physical properties such as mechanical properties, etc. Also, it is possible to provide a heat-shrinkable label including the heat-shrinkable film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0071] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the examples and reference examples, the following raw materials were used.

[0072] (Polyester resin) PET-1: Biomass-containing polyester resin (100 mol% dicarboxylic acid derived from terephthalic acid, 100 mol% diol derived from ethylene glycol, glass transition temperature: 75°C) PET-2: Biomass-free polyester resin (100 mol% dicarboxylic acid derived from terephthalic acid, 100 mol% diol derived from ethylene glycol, glass transition temperature: 75°C) PET-3: Biomass-containing polyester resin (Dicarboxylic acid component derived from terephthalic acid: 77 mol%, diol component derived from ethylene glycol: 100 mol%, glass transition temperature: 71°C) PET-4: Biomass-free polyester resin (Dicarboxylic acid components derived from terephthalic acid: 77 mol%, diol components derived from ethylene glycol: 100 mol%, glass transition temperature: 71°C) PET-5: Biomass-free polyester resin (dicarboxylic acid component derived from terephthalic acid: 100 mol%, diol component derived from ethylene glycol: 65 mol%, diethylene glycol: 20 mol%, 1,4-cyclohexanedimethanol: 15 mol%, glass transition temperature: 69°C)

[0073] (Polystyrene resin) PS-1: Styrene-butadiene copolymer not containing biomass components (styrene component: 76% by weight, butadiene component: 24% by weight, Vicat softening temperature: 70°C) PS-2: Styrene-butadiene copolymer containing no biomass components (styrene component: 70% by weight, butadiene component: 30% by weight, Vicat softening temperature: 72°C) PS-3: Styrene-butadiene copolymer containing no biomass components (styrene component: 84% by weight, butadiene component: 16% by weight, Vicat softening temperature: 75°C) PS-4: Styrene-butadiene copolymer containing biomass components (styrene component: 75% by weight, butadiene component: 25% by weight, Vicat softening temperature: 62°C) PS-5: Styrene-butadiene copolymer containing biomass components (styrene component: 90% by weight, butadiene component: 10% by weight, Vicat softening temperature: 72°C)

[0074] (Examples 1 to 5, Reference Examples 1 to 3) The polyester resins shown in Table 1 were used as the resins constituting the front and back layers. As the resin constituting the intermediate layer, a polystyrene resin shown in Table 1 was used. These were fed into an extruder with a barrel temperature of 160 to 250°C, extruded from a multilayer die at 250°C into a three-layered sheet, and cooled and solidified by a take-up roll at 30°C. Next, the film was stretched at a stretch ratio of 6 times in a tenter stretching machine with a preheating zone of 115°C, a stretching zone of 90°C, and a heat setting zone of 85°C, and then taken up by a winding machine to obtain a heat-shrinkable multilayer film in which the direction perpendicular to the main shrinkage direction is MD and the main shrinkage direction is TD. The obtained heat-shrinkable film had a total thickness of 40 μm and a three-layer structure with a layer ratio (thickness ratio) of front / back layer / intermediate layer / front / back layer = 1 / 5 / 1 and a layer ratio (weight ratio) of front / back layer / intermediate layer / front / back layer = 1 / 6 / 1.

[0075] (Examples 6 and 7, Reference Example 4) The polyester resins shown in Table 1 were used as the resins constituting the heat-shrinkable films. This was fed into an extruder with a barrel temperature of 160 to 250° C., extruded from a single-layer die at 250° C. into a single-layer sheet, and cooled and solidified by a take-up roll at 30° C. Next, the film was stretched at a stretch ratio of 6 times in a tenter stretching machine with a preheating zone of 115° C., a stretching zone of 90° C., and a heat setting zone of 85° C., and then taken up by a winding machine to obtain a heat-shrinkable multilayer film in which the direction perpendicular to the main shrinkage direction is MD and the main shrinkage direction is TD. The resulting heat shrinkable film had a total thickness of 40 μm.

[0076] (Examples 8 and 9, Reference Example 5) As the resin constituting the heat shrinkable film, a polystyrene resin shown in Table 1 was used. These were fed into an extruder with a barrel temperature of 160 to 250°C, extruded from a single-layer die at 250°C into a single-layer sheet, and cooled and solidified by a take-up roll at 30°C. Next, the film was stretched at a stretch ratio of 6 times in a tenter stretching machine with a preheating zone of 115°C, a stretching zone of 90°C, and a heat setting zone of 85°C, and then taken up by a winding machine to obtain a heat-shrinkable multilayer film in which the direction perpendicular to the main shrinkage direction is MD and the main shrinkage direction is TD. The resulting heat shrinkable film had a total thickness of 40 μm.

[0077] (evaluation) The heat-shrinkable films obtained in the Examples and Reference Examples were evaluated as follows. The results are shown in Table 1.

[0078] (1) Biomass ratio The biomass degree of the obtained heat-shrinkable film was measured by determining the concentration of radioactive carbon (C14) using an accelerator mass spectrometer (NEC, 9SDH-2) based on ISO16620-2:2015.

[0079] (2) Heat shrinkage rate The obtained heat-shrinkable film was cut into a size of 100 mm x 100 mm and immersed in hot water at 70°C, 80°C, 90°C, and 98°C for 10 seconds each, and then the heat-shrinkable film was taken out and the ratio of the dimension after heating to the dimension before heating was calculated. The shrinkage rate was calculated by averaging three samples.

[0080] (3) Hayes The haze of the obtained heat shrinkable film was measured using a haze meter (NDH-5000, manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS K-7136 (2000).

[0081] [Table 1] [Industrial Applicability]

[0082] According to the present invention, it is possible to provide a heat-shrinkable multilayer film that can reduce the amount of fossil resources used and exhibit high performance in terms of physical properties such as mechanical properties, etc. Also, it is possible to provide a heat-shrinkable label including the heat-shrinkable film.

Claims

1. A heat-shrinkable film having at least one layer selected from a layer containing a polyester-based resin and a layer containing a polystyrene-based resin, The heat shrinkable film contains a component derived from biomass. A heat shrinkable film characterized by:

2. The sheet has front and back layers containing a polyester resin and an intermediate layer containing a polystyrene resin, At least one of the polyester-based resin and the polystyrene-based resin contains a component derived from biomass.

2. The heat shrinkable film according to claim 1.

3. 3. The heat-shrinkable film according to claim 1, wherein the biomass ratio is 1 to 50%.

4. A heat-shrinkable label comprising the heat-shrinkable film according to claim 1, 2 or 3.

Citation Information

Patent Citations

  • Heat shrinkable laminated film, molded article using the same and heat shrinkable label and container

    JP2006015745A

  • Production method for raw material of resin, and resin and its production method

    JP2007176873A

  • Heat-shrinkable multilayer film and heat-shrinkable label

    JP2009000898A

  • Heat-shrinkable laminated film, molding and label using the film, and vessel with the molding and label attached thereto

    JP2010214900A

  • Cap tread rubber composition for passenger car tire, cap tread rubber for passenger car tire, and pneumatic tire for passenger car

    JP2015042711A